(untitled) (Margalla Papers, 2023)
The book “The Security Imperative: Pakistan’s Nuclear Deterrence and Diplomacy” is a landmark book by Pakistan’s renowned ambassador Zamir Akram who is currently an advisor to the Strategic Plans Division (SPD) Pakistan. The motive of writing the book, as the author postulates, was to fill the void of literature in the domain of nuclear diplomacy of Pakistan especially left by most of the Pakistani authors, and to exhibit the actual face of Pakistan’s Nuclear Program to the world. The author argues that the book is based on 38 years of experience of the author in the foreign service of Pakistan and deeply relies on declassified official documents, interviews with key players and on secondary and empirical data. Bibliography Entry Meer, Shah. 2023. "The Security Imperative: Pakistan’s Nuclear Deterrence and Diplomacy." Margalla Papers 27 (2): 132-133.